2020
DOI: 10.1016/j.psj.2020.06.061
|View full text |Cite
|
Sign up to set email alerts
|

In ovo supplementation of chitooligosaccharide and chlorella polysaccharide affects cecal microbial community, metabolic pathways, and fermentation metabolites in broiler chickens

Abstract: The chitooligosaccharide ( COS ) and chlorella polysaccharide ( CPS ) have been used as feed supplements in the poultry industry for improving growth performance and immunity. However, the benefits of these prebiotics on the gut health of chickens when used in early nutrition are unknown. This study evaluated the effects of in ovo feeding of COS and CPS on the cecal microbiome, metabolic pathways, and fermentation metabolites of chickens. A total of 240 fertile egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 44 publications
0
44
0
Order By: Relevance
“…Likewise, Huang et al ( 23 ) and Li et al ( 24 ) found that the dietary inclusion of 150 or 100 mg/kg COS improved ADG and FCR in broilers. A wide range of mechanisms can underlay to decipher the beneficial effects of these natural marine polysaccharides on enhancing the growth performances, antioxidant capacity, and intestinal health status ( 22 ), promoting the growth of beneficial gut microbiota ( 8 ), immunity ( 14 , 21 ), and nutrient digestibility ( 15 ) in broilers. However, Biggs et al ( 25 ) and Shang et al ( 6 ) observed no significant difference in the growth performance of broiler chickens fed a diet containing natural polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, Huang et al ( 23 ) and Li et al ( 24 ) found that the dietary inclusion of 150 or 100 mg/kg COS improved ADG and FCR in broilers. A wide range of mechanisms can underlay to decipher the beneficial effects of these natural marine polysaccharides on enhancing the growth performances, antioxidant capacity, and intestinal health status ( 22 ), promoting the growth of beneficial gut microbiota ( 8 ), immunity ( 14 , 21 ), and nutrient digestibility ( 15 ) in broilers. However, Biggs et al ( 25 ) and Shang et al ( 6 ) observed no significant difference in the growth performance of broiler chickens fed a diet containing natural polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Natural polysaccharides, which are widely distributed in the microorganisms and plants, can improve an animal's gut health (4). Previously, numerous studies found that the natural polysaccharides derived from plants and fungus could be used as prebiotics to improve gut microflora balance and barrier function, ultimately promoting the growth of broiler chickens (5)(6)(7)(8). Therefore, these natural and functional polysaccharides could replace antibiotics in the poultry industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, different nutrients and feed additives have been used to optimize the gastrointestinal integrity and immune system of young animals ( Adedokun and Olojede ). However, gut microbiota plays a significant role in managing the gut environment by producing fermentation metabolites and influencing nutrient utilization pathways ( 18 ). Thus, it is important to understand the gut microbial ecology in-depth, including their taxonomic composition and biochemical functions.…”
Section: Importance and Understanding The Intestinal Health Of Young mentioning
confidence: 99%
“…Thus, it is important to understand the gut microbial ecology in-depth, including their taxonomic composition and biochemical functions. However, the gut microbiota is primarily influenced by diet, age, species, and location in the digestive tract ( 5 , 18 , 19 ). Different techniques have been used to characterize the gut microbiota, but those have different strengths and limitations.…”
Section: Importance and Understanding The Intestinal Health Of Young mentioning
confidence: 99%